Usability Testing of the E-learning System at SMK TI Bali Jimbaran Using the Concurrent Think Aloud (CTA) and System Usability Scale (SUS) Methods - I Putu Agus Eka Yatna Cipta; Rifky Lana Rahardian; Aldho Wardana; Muhammad Agha Firmansyah; I Made Arya Satyana (Institut Agama Islam Negeri Ponorogo, 2026)
E-learning serves as a support tool for teachers in fulfilling their responsibilities as educators and homeroom teachers. This system has been implemented as a learning medium; however, some users, particularly new users, still experience difficulties adapting to its interface, which differs from those of commonly used systems. This study aims to evaluate the e-learning system of SMK TI Bali Global Jimbaran in terms of effectiveness, efficiency, and user satisfaction. The usability testing method was selected to evaluate the system based on these three aspects. The techniques used in this study include Concurrent Think Aloud (CTA) and the System Usability Scale (SUS). This evaluation used a sample of 20 teacher respondents. The sample was separated by level of technology proficiency: 10 representatives from the advanced group and 10 representatives from the beginner group. In qualitative research, including CTA, the number of participants is determined based on the principle of data saturation, which occurs when the collected data begin to show repetitive patterns and no significant new findings emerge. With 15–20 users, coverage of usability problems can reach nearly 100% of relevant issues. Therefore, 20 participants are considered sufficient to ensure that the major usability problems in the e-learning system have been identified. To measure user satisfaction, the System Usability Scale (SUS) method was employed, while interface improvement recommendations were derived using the Concurrent Think Aloud (CTA) method. The respondents involved in the SUS method were the same as those participating in the CTA method. The results of the CTA and SUS analyses will serve as a basis for recommendations to improve the e-learning system in the future.